Sentential Derivation (logic) help please

I really can't figure this derivation out.

Assumptions:

1. $\displaystyle \neg (F \vee G)$ iff $\displaystyle (\neg F \supset \neg F)$

2. $\displaystyle \neg G \supset F$

I need to derive contradicting sentences to show that it is inconsistent, I can tell it is since $\displaystyle \negF\supset\negF$ is always true, which means ~(F v G) is true, so F and G both have to be false individually, which would contradict the $\displaystyle \neg G \supset F$ since ~G would be true and F is false.

However, I don't know how to formulate this in SD (going by The Logic Book 5th edition by Bergmann). Can anyone help?

Thanks in advance!